2010
DOI: 10.1097/01.aids.0000390705.73759.2c
|View full text |Cite
|
Sign up to set email alerts
|

Postexposure prophylaxis, preexposure prophylaxis or universal test and treat: the strategic use of antiretroviral drugs to prevent HIV acquisition and transmission

Abstract: This review considers the use of antiretroviral drugs specifically to prevent HIV transmission. Antiretroviral therapy (ART) can be implemented for the protection of uninfected individuals both before (preexposure prophylaxis) and after (postexposure prophylaxis) exposure to HIV infection. Preexposure prophylaxis may be used coitally dependently when individuals are intermittently exposed or by continuous daily dosing for those constantly exposed; postexposure prophylaxis is used in 28-day courses. Alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 91 publications
0
21
0
3
Order By: Relevance
“…34 The implications of this finding for HIV prevention in MSM are not immediately clear. Very few same-sex couples were included in the study, and a separate analysis of efficacy in MSM was not possible.…”
Section: Antiretroviralsmentioning
confidence: 99%
“…34 The implications of this finding for HIV prevention in MSM are not immediately clear. Very few same-sex couples were included in the study, and a separate analysis of efficacy in MSM was not possible.…”
Section: Antiretroviralsmentioning
confidence: 99%
“…Yet recent studies have found that 8–20 % of MSM had never been tested for HIV and only 60 % had been tested in the past 12 months [32, 61, 62]. Post-exposure prophylaxis [PEP], the provision of antiretroviral drugs after a possible exposure to HIV [63, 64], can stop an HIV infection from taking hold if taken within 1–3 days of exposure [59, 63, 65–67]. In a range of studies among MSM, 36–48 % of participants said they were aware of PEP [68–70] but only 1.9–6.3 % had used it [32, 68, 69, 71, 72] reflecting a broader trend in which use of PEP by MSM has remained well below 10 %.…”
Section: Introductionmentioning
confidence: 99%
“…While antiretroviral drugs have shown efficacy in the treatment of HIV infection, antiretroviral drugs have also been successfully used for HIV prevention in a variety of settings, including pre-exposure prophylaxis in HIV-uninfected individuals (PrEP) and as ‘treatment as prevention’ in HIV-infected individuals, following either oral or vaginal administration [6-12]. Topical microbicides are vaginally or rectally administered products designed to prevent HIV transmission at the site of acquisition [2,13-15].…”
mentioning
confidence: 99%